The radiation and biogeography of snakes across south-eastern Africa with respect to the evolution of the savanna biome - Engelbrecht, Hanlie M. (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.